POSTER: MEDIA DAKWAH PEMUDA HIJRAH - Ulya, Fina (Kopertais Wilayah III Yogyakarta, 2023)
The hijrah movements among Indonesian Moslem young have continuously begun to bloom in several regions in Indonesia. One of the hijrah movement communities is SHIFT: Gerakan Pemuda Hijrah, which brings popular cultures and spreads Islamic teachings to the majority of the millennial generations. Not only the way they teach, the media they use is also been an crucial factor in making the younger generation follow and pay attention to their teachings. The spirit of SHIFTs’ preaching can be analyzed through such posters as the illustration of vodka under banner of Kajian Spesial bersama Ustadz Evie, Raos tapi Dosa; or a poster that mentions a cigarette brand, yet written warning: menjomblo terlalu lama sendiri dapat mengakibatkan galau kronis, masa depan suram, merasahkan warga, bangsa & orang tua. This research explores more analytically the content of motivation written in the SHIFTs’ posters within semiotics analysis. After analyzing the significance and signs of these posters, this research proves that there is a relationship between the motivation to emigrate and the new spirit of piety offered by the emigration youth movement. Keywords: Poster, Piety, Shift, Young.